Aestivation induces widespread transcriptional changes in the African lungfish - Niu, Yuhan; Guan, Lihong; Wang, Cheng; Jiang, Haifeng; Li, Guogang; Yang, Liandong (Frontiers in Genetics, 2023)
Aestivation is a special ability possessed by some animals to cope with hot and dry environments utilizing dormancy. At a macroscopic level, dormant animals stop moving and eating. At the microscopic level, the expression of a large number of genes in these animals is strictly controlled. However, little is known about what changes occur during aestivation, especially in fish. In this study, we used transcriptome analysis to examine what changes occur in the gills and lungs of the African lungfish (Protopterus annectens) during the maintenance phase of aestivation and speculated on their causes. We found that aestivating transcriptomes were highly similar between gills and lungs. We also found that some genes showed differential expression or alternative splicing, which may be associated with different organs. In addition, differential expression analysis revealed that the lungs maintained significantly higher bioactivity during aestivation, which suggests that the main respiratory organ in aestivating lungfish can transform. Our study provides a reference point for studying the relationship between aestivation and hibernation and further increases understanding of aestivation.